Efektivitas Tanaman Kayu Apu (Pistia stratiotes L.) Terhadap Penurunan Kadar COD dan BOD Menggunakan Metode Fitoremediasi pada Limbah Cair Industri Tahu Tahun 2025 - Purba, Bahtera Bindavid; Sembiring, Ripando Jon Satria; Malau, Pitto (Jurnal Penelitian Kesmasy, 2025)
Liquid waste from tofu industries contains high levels of organic matter, as indicated by COD (Chemical Oxygen Demand) and BOD (Biochemical Oxygen Demand) values that exceed environmental quality standards. This can lead to water pollution and harm aquatic ecosystems. This study aims to determine the effectiveness of water lettuce (Pistia stratiotes L.) in reducing COD and BOD levels in tofu industry wastewater through the phytoremediation method. The research was conducted using a post-test only experimental design. The Treatments were applied by placing 500 grams of water lettuce into the wastewater for durations of 3, 6, and 9 days. The results showed that COD levels decreased from 784 mg/L to 132 mg/L on the 9th day (a reduction of 83.16%), and BOD levels decreased from 272 mg/L to 41 mg/L (a reduction of 84.92%). The findings indicate that water lettuce is effective in lowering COD and BOD levels, and the duration of exposure significantly affects the level of effectiveness. Phytoremediation using water lettuce can be a simple, environmentally friendly, and cost-effective alternative for treating liquid waste, especially in small-scale or household tofu industries.